(untitled) (Delta Medical College Journal, 2020)
Rickettsial diseases are a group of infections caused by the obligate intracellular bacteria Rickettsia. Rickettsial infections are common in southern Europe. The disease is usually characterized by the classical triad of fever, eschar and rash. Complications including neurological involvement are rarely described. We report an unusual case of meningitis in a 55 years old man presenting with high grade fever for 8 days associated with persistent headache. The patient was suspected to have enteric fever and treated with injection ceftriaxone. Forty-eight hours after admission, the presence of continued high grade fever, conjunctival congestion, headache, cough, low platelet and increased WBC count, and elevated transaminase raised the possibility of a different aetiology. Finally, Rickettsial meningitis was confirmed due to history of field visit, presence of eschar, neck rigidity, raised titre of WF OX-K antigen and the cerebrospinal fluid analysis revealed increased cellularity, hypoglycorrhachia, and hyper proteinorrhachia (106 mg/dL). Patient was treated with capsule doxycycline and other supportive therapy and became afebrile within 48 hours. This uncommon clinical scenario should be taken into account in the management of patients with high grade fever on admission. Delta Med Col J. Jul 2019 7(2): 100-103